Translation Challenges of Political Terms between Arabic and English: A Comparative Analytical Study in Diplomatic Discourse - -Aldulaimi, Sarah Khalid khudhair (The International and Political Journal, 2025)
In this paper, the researcher examines the issues that render political phrases between Arabic and English into diplomatic speeches. Research employs comparative method of analysis, based on selected speeches, treaties and diplomatic statements. This research paper identifies the linguistic, cultural and ideological constraints that tend to block the proper translation. The practical challenges which translators might encounter in the suggested equivalent strategy are considered with particular attention to the research of scholars of translation and the actual political realities. Allusions to the past work of the University of Al-Mastansaria are also incorporated in order to have a local educational outlook. Results indicate that translation of politics necessitates not just linguistic competency, but also cultural sensitivity, situational sensitivity and diplomatic apathy. This analysis finishes with the suggestion of translation and translation of the diplomatic practice.